Substrate Type Influences the Structure of Epiphyte Communities and the Growth of Posidonia oceanica Seedlings - De Battisti, Davide; Balestri, Elena; Pardi, Giuseppina; Menicagli, Virginia; Lardicci, Claudio (Frontiers in Plant Science, 2021)
Epiphytes colonizing adult seagrasses highly contribute to seagrass ecosystem functioning and plant growth. Yet, little information exists on epiphytic communities developing on seagrass seedlings. Moreover, for some species our knowledge about seedling performance is limited to early establishment phases, and the role of substrate type in affecting their growth is still unclear. These are considerable knowledge gaps, as seedlings play an important role in meadow expansion and recovery from disturbance. In this study, seedlings of Posidonia oceanica, a keystone species of the Mediterranean, were grown in a shallow (1.5 m deep) coastal area along the Tuscany coast (Italy). After five years of growth (July 2009), seedlings were collected and, through multivariate analysis, we examined whether the epiphytic communities of leaves (both internal and external side) and rhizomes, as well as the growth characteristics differed between rock and sand substrate. The epiphytic communities of seedlings largely reflected those found on adult shoots. Epiphyte cover was similar between the two leaf sides, and it was higher on seedlings grown on rock than on sand, with encrusting algae dominating the community. No differences in epiphyte cover and community structure on rhizomes were found between substrates. Seedling growth characteristics did not differ between substrates, apart from the number of standing leaves being higher on rock than on sand. No correlation was found among epiphyte communities and seedling growth variables (i.e., leaf area, maximum leaf length, number of leaves, total number of leaves produced, rhizome length, total biomass, and root to shoot biomass ratio). Results indicate that seedlings successfully colonise P.oceanica seedlings, and the surrounding micro-environment (i.e., substrate type) can influence the leaf epiphytic community. This study provides new valuable insights on the biological interactions occurring in seagrass ecosystems and highlight the need for better the effects of seedling epiphytes and substrate on the formation of new meadows.